Synthesis of a superphane dimer: a metallocenophane with four metal centers - Roers, Rolf; Hofmann, Jasmin; Claßen, Jörg; Gleiter, Rolf (Tetrahedron letters, 2001)
The first dimeric bis(η5-cyclopentadienyl-η4-cyclobutadienyl–cobalt)superphane has been synthesized. It represents a metallocenophane with four cobalt centers which are electrochemically active. Cyclic voltammetric (CV) studies revealed two reversible oxidation potentials at 500 and 870 mV and two irreversible peaks at 1050 and 1280 mV, respectively.